Influence of Different Types of Emulsifiers on Properties of Emulsified Asphalt Binder and Its Evaporation Residue by Molecular Dynamics Simulation - Ying-feng Wu; Xin Qu (Advances in Materials Science and Engineering)
There is an important role in the properties of emulsified asphalt binder and its evaporation residue about emulsifier, which has been confirmed by experiment and chemical tests. However, there is little research about the emulsifier at microperspective. Therefore, the influence of two kinds of emulsifiers, a typical cationic emulsifier (dodecyl benzene sulfonate) and a typical anionic emulsifier (dodecyl primary amine), on technical properties of emulsified asphalt binder and its evaporation residues such as store stability, workability, breaking behavior, and mechanical properties are investigated using a microapproach. Results show that there is an effective role in the storage stability, workability, and demulsification of emulsified asphalt binder about cationic emulsifier compared with anionic emulsifier. The anionic emulsifier makes the density of evaporation residue larger. However, the mechanical properties of anionic emulsified asphalt evaporation residue are conversely smaller compared with the cationic emulsified asphalt evaporation residue. The adhesion behavior results have confirmed that the anionic emulsified asphalt evaporation residue has a negative adhesion with aggregate due to its anion. The mechanism of the different emulsifiers on asphalt binders and their evaporation residue is explored at a microscale to help us to understand emulsified asphalt binder and its evaporation residue more in depth.